Reading motivation and reading comprehension achievement among English majors in China: A descriptive correlational study - Lei Ma; Zheng Zhao (Heliyon)
This study explores the relationship between reading motivation and reading comprehension achievement among English major students in China, an area that has received limited attention in existing literature. Drawing on previous research emphasizing the importance of reading motivation in improving reading skills, this study seeks to examine the connection between reading motivation and reading comprehension achievement within the specific research context. The Pearson correlation coefficient showed a significant positive correlation between reading motivation and reading proficiency among English major students at a Chinese private undergraduate university. The study also indicated that reading motivation can predict reading comprehension scores. This investigation not only fills a gap in current research but also paves the way for future experimental studies to investigate the efficacy of specific motivational interventions or instructional strategies in boosting reading motivation and subsequently improving reading skills among English language learners. The findings of this study are expected to guide educational practices and policies, ultimately leading to advancements in English language education for Chinese students majoring in English.